Możliwości publicznego wsparcia funduszy venture capital tworzonych przez Agencje Rozwoju Regionalnego - Świderska, Joanna (Regional Development Agencies Public Support for Venture Capital Funds, 2006)
Over 140 active regional development agencies play a significant role in the economic growth support in Poland. These institutions are deeply rooted in entrepreneurs consciousness, have self-government support and experience in financial and non-financial support of SME sector. The range of agencies activities is wide, beginning with information services, advisory, trainings, financial services, for creating independent capital funds providing venture capital activities. Lubelski Capital Fund Ltd. and Podlaski Capital Fund Ltd. are classic examples of effective capita] funds created within a regional development agency group. The analysis of their activities allows assuming that expanding the network of this kind of funds is a need in Poland. That is why effective EU funds management becomes more and more important. One of the possibilities of support is given by 1.2.3 Activity "Support of seed capital funds creating" that was planned to be implemented within Priority 1 of Sector Operational Program - Enterprises Competitiveness Development. The implementing institution is Polish Agency for Enterprise Development with a restriction that its duties will be held by Domestic Capital Fund Inc. (being registered at the moment). Comparing conditions of financial support provided by 1.2.3 Activity and by Domestic Capital Fund Inc. it is clearly visible that two different ways of venture capital funds financial support become reality which is opposite to the earlier assumptions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 517-528